PENGARUH BEBAN OPERASIONAL/PENDAPATAN OPERASIONAL (BOPO) TERHADAP KINERJA KEUANGAN PADA PT BANK RAKYAT INDONESIA TBK (PERIODE 2017-2022) - Mirah, Mirah; Ayunani, Faras Zulina (Aliansi : Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the partial and simultaneous effect of Operational Expenses/Operating Income (BOPO) on Financial Performance at PT Bank Rakyat Indonesia Tbk (2017-2022 Period). This study uses secondary data. The population in this study is the Financial Statements of Bank Rakyat Indonesia which are registered with BRI. The technique used to analyze the data used is the classical assumption test and simple linear regression test. The results of this study indicate that partially BOPO has a significant effect on ROA. The results of the t test were obtained at -6.985. The t-test significance value was obtained at 0.002. A significance value of less than 0.05 indicates that BOPO has a significant effect on ROA. Meanwhile simultaneously BOPO has an effect on ROA. The results of the F test were 48.787. The F value of the significance of the test was obtained at 0.002. A significance value greater than 0.05 indicates that BOPO has a significant effect on ROA.